Phytochemical studies on Stemona aphylla: Isolation of a new stemofoline alkaloid and six new stemofurans - Thanapat Sastraruji (2018)
A new stemofoline alkaloid, (2'S)-hydroxy-(11S,12R)-dihydrostemofoline (3), new stemofurans M-R (8-13), and known compounds stemofoline (1), (2'S)-hydroxystemofoline (2), stemofuran E (4), stemofuran F (5), stemofuran J (6), and stilbostemin F (7) have been isolated from the root extracts of Stemona aphylla. The structures and relative configurations of these new compounds have been determined by spectroscopic data interpretation and from semisynthetic studies. These natural and semisynthetic alkaloids were tested for acetylcholinesterase inhibitory activities and were found to be 10-20 times less active than 1',2'-didehydrostemofoline itself. Stemofurans 4, 6, 8, 11, and 13 were tested for their antibacterial and antifungal activities. Three of these showed antibacterial activities against MRSA with MIC values of 15.6 μg/mL. © 2011 American Chemical Society and American Society of Pharmacognosy.